The association between self-reported sleep problems, infection, and antibiotic use in patients in general practice - Forthun, Ingeborg; Eliassen, Knut Eirik Ringheim; Emberland, Knut Erik; Bjorvatn, Bjørn (Frontiers in Psychiatry, 2023)
Objectives: There is emerging evidence that sleep problems and short sleep duration increase the risk of infection. We aimed to assess whether chronic insomnia disorder, chronic sleep problems, sleep duration and circadian preference based on self-report were associated with risk of infections and antibiotic use among patients visiting their general practitioner (GP). Methods: We conducted a cross-sectional study of 1848 unselected patients in Norway visiting their GP during 2020.The patients completed a one-page questionnaire while waiting for the consultation, that included the validated Bergen Insomnia Scale (BIS), questions on self-assessedassessed sleep problem, sleep duration and circadian preference and whether they have had any infections or used antibiotics in the last three months. Relative risks (RR) were estimated using modified Poisson regression models. Results: The risk of infection was 27% (95% CI RR 1.11-1.46) and 44% higher (95% CI 1.12-1.84) in patients sleeping <6 hours and >9 hours, respectively, compared to those sleeping 7-8 hours. The risk was also increased in patients with chronic insomnia disorder or a chronic sleep problem. For antibiotic use, the risk was higher for patients sleeping <6 hours, and for those with chronic insomnia disorder or a chronic sleep problem. Conclusions: Among patients visiting their GP, short sleep duration, chronic insomnia and chronic sleep problem based on self-report were associated with higher prevalence of infection and antibiotic use. These findings support the notion of a strong association between sleep and infection.